Acerca del status ontológico de las entidades químicas: el caso de los orbitales atómicos - Labarca, Martín Gabriel (2010)
The aim of the present paper is to analyze the problem of the relationship between chemistry and physics, by focusing on the widely discussed case of the atomic orbitals. We will begin by remembering the difference between the physical and the chemical interpretation of the concept of orbital. Then, we will refer to the claim made in 1999 that atomic orbitals have been directly imaged for the first time. On this basis, we will analyze the problem from a new approach, by comparing the concept of orbital used in physics with the concept of orbital used in chemistry. Such an analysis will allow us to argue for an ontological pluralism that admits the coexistence of different ontologies without priorities or metaphysical privileges. From this philosophical framework, the concepts of chemical orbital and physical orbital correspond to two different ontologies. As a consequence, chemical orbitals are real entities belonging to the ontology of molecular chemistry, and can be observed like any other entity not belonging to the quantum mechanical ontology.